Malaysia: Cassava vs. tree crops in the competition for land - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
The agricultural economy of Malaysia has traditionally been export-oriented. Cassava was the 1st of the export crops, established in the 1850s. Malaysia is a land-surplus, labor-scarce economy; thus cassava was planted in a shifting cultivation system giving it the image of a soil-depleting crop. Data are also provided on yields, production systems, production costs and labor utilization, and pricing and market efficiency. The national plan through 2000 emphasizes tree crops, which could affect cassava production. (CIAT)